2019
DOI: 10.1177/0003489419858090
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of European Otolaryngologists and General Practitioners Toward Laryngopharyngeal Reflux

Abstract: Objectives: To investigate the current trends in management of laryngopharyngeal reflux (LPR) among young European otolaryngologists and general practitioners (GP). Methods: An international survey was sent to European general practitioners and all otolaryngologists under 45 years old from the 2017 IFOS meeting. This survey was conducted by the LPR Study Group of YO-IFOS (Young Otolaryngologists of the International Federation of Otolaryngological Societies). Results: Among the 2500 attendees, 230 European oto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 37 publications
2
30
0
1
Order By: Relevance
“…In a recent study, significant differences in awareness and practices regarding LPR were observed between European otolaryngologists and general practitioners (GPs). Of particular note, only 10.1% of GPs and 27.4% of otolaryngologists believed that they were adequately knowledgeable and skilled regarding LPR [15]. This is the first study designed to investigate current practices and opinions of Asian otolaryngologists regarding LPR.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a recent study, significant differences in awareness and practices regarding LPR were observed between European otolaryngologists and general practitioners (GPs). Of particular note, only 10.1% of GPs and 27.4% of otolaryngologists believed that they were adequately knowledgeable and skilled regarding LPR [15]. This is the first study designed to investigate current practices and opinions of Asian otolaryngologists regarding LPR.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent systematic review, the most prevalent LPR symptoms were found to be globus sensation, throat clearing, hoarseness, excess throat mucus, and postnasal drip [9], while more than 70% of the Asian otolaryngologists surveyed in this study considered coughing after lying down or after eating, throat clearing, globus sensation, and chronic cough to be LPR-related symptoms. Interestingly, the opinions of Asian and European otolaryngologists about LPR-related symptoms differ [15]. Stomach acid coming up, cough, hoarseness, and throat pain were considered to be the symptoms most closely related to LPR by European otolaryngologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few studies investigated the potential differences between these two types of LPR patients. This lack of interest is probably related to the low use of pH monitoring or MII‐pH in otolaryngology, which are indispensable to make the GERD diagnosis. Moreover, the recent development of MII‐pH in gastroenterology led to the identification of three LPR subtypes, acid, nonacid, and mixed LPR, regarding the proportion of proximal acid or nonacid reflux episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that LPR is not an extension of the lower esophageal refluxate into the upper aerodigestive tract. The Montreal criteria defined GERD as a condition that develops when the reflux of stomach contents causes troublesome symptoms and/or complications such as esophagitis [19,20]. The diagnosis may be investigated with pH study that, according to Johnson et DeMeester, has to report a length of time >4.0% of the 24-h recording spent below pH 4.0 or a DeMeester score >14.72 [21].…”
Section: Lpr Is Not Gerd and Gerd Is Not Lprmentioning
confidence: 99%